Integrating Lean Six Sigma and Soil Quality Preservation in Topsoil Removal Operations: A Case Study of Indonesian Coal Mining - Menahim Fajar Kurnia Rapa; Noorhan Firdaus Pambudi (Devotion : Journal of Research and Community Service, 2026)
Topsoil removal is a critical activity in surface coal mining operations because it directly affects operational productivity and the success of post-mining land rehabilitation. This study aimed to identify operational waste within the topsoil removal process, develop improvement strategies to enhance productivity, and evaluate the role of soil quality preservation in supporting sustainable mining practices. The study employed a Lean Six Sigma framework using the DMAIC (Define, Measure, Analyze, Improve, Control) methodology. Value Stream Mapping (VSM), Cycle Time Analysis, Pareto Analysis, and Failure Mode and Effects Analysis (FMEA) were applied to identify process inefficiencies, prioritize critical operational issues, and formulate improvement strategies. The findings revealed that approximately 43.37% of the total operational cycle time consisted of non-value-added activities, with the dominant sources of waste occurring in loading queue time, traffic conflicts at intersections shared with overburden hauling operations, haul road-related travel delays, blasting interruptions, and operator-related delays. The FMEA results further identified loading queue time (RPN = 324), traffic conflicts (RPN = 320), and haul road delays (RPN = 280) as the most critical operational risks. The proposed improvement initiatives were estimated to reduce cycle time by approximately 20% and increase hauling productivity by around 24%. Beyond productivity improvement, this study highlighted the importance of preserving topsoil quality through controlled handling practices and the application of lower-impact equipment to minimize soil compaction and maintain humus integrity. The findings demonstrated that operational efficiency and soil quality preservation could be achieved simultaneously through a systematic Lean Six Sigma approach, contributing to sustainable mining operations and successful post-mining land reclamation.